Optimizing aquaculture-scale common carp artificial reproduction: a novel approach to sperm cryopreservation using large-volume containers and elevated thawing temperatures - Sotnikov, Anatolii; Rodina, Marek; Gela, David; Boryshpolets, Sergii; Kholodnyy, Vitaliy; Kašpar, Vojtěch; Linhart, Otomar; Dzyuba, Borys (Frontiers in Marine Science, 2024)
Introduction The successful cryopreservation of common carp sperm is crucial for its application in aquaculture and selective breeding programs. This study investigates the efficacy of cryopreserving sperm in large containers (5 mL) with a low dilution rate (1:1) in three different cryoprotective media and thawing in different conditions. Methods The developed method utilizes a low-ionic (hypotonic) cryoprotective medium, freezing with a controlled cooling rate, and high-temperature sperm thawing (60°C). The investigation employs a detailed spermatozoon motility assessment. Results Post-thaw motility of 32.3% ± 14% and initial curvilinear velocity of 89 ± 20 μm/s across 30 males were observed. Principal component analysis of sperm kinematic characteristics revealed distinct populations of sperm cells exhibiting varying responses to cryopreservation. The developed method achieved successful fertilization comparable to that of the non-frozen control group using sperm from a single cryotube (2.5 mL, approximately 50 * 109 spermatozoa) to fertilize 200 g of eggs (1:120,000 egg:spz). Discussion This novel approach demonstrates an effective cryopreservation protocol for common carp sperm in large-volume cryo-containers in combination with low-ionic cryomedia and high thawing temperature, providing methods well-suited for fisheries practices and selective breeding programs. Future studies of the biological properties of different sperm subpopulations in post-thaw sperm samples can contribute to a deeper understanding of sperm biology, improve cryopreservation techniques, and enhance the success rates of assisted reproductive technologies.